2017
DOI: 10.3390/polym9060211
|View full text |Cite
|
Sign up to set email alerts
|

DNA Binding with Acetate Bis(1,10-phenanthroline)silver(I) Monohydrate in a Solution and Metallization of Formed Structures

Abstract: Abstract:The study of DNA interaction with the acetate bis(1,10-phenanthroline)silver(I) monohydrate in a solution is of interest both for understanding the mechanism of biological activity of silver compound and for forming ordered structures (DNA fibrils) that can be used to solve various problems in the field of nanotechnology. The analysis of changing the DNA conformation (secondary structure, persistent length and volume effects) during the interaction by the methods of UV spectroscopy with the analysis o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 59 publications
(71 reference statements)
0
12
0
Order By: Relevance
“…Different procedures have been utilized to incorporate metal ions, such as silver, into DNA strands to construct metal nanostructures. Kasyanenko et al [ 76 ] bound bis(1,10-phenanthroline) silver(I) (Ag-Phen) to DNA in solution where the phenanthroline ligands allowed for uniform binding of silver on DNA structures. The Ag-Phen-DNA complexes were treated with sodium borohydride to reduce Ag metal on DNA fibrils.…”
Section: Metallization Of Dna Templatesmentioning
confidence: 99%
“…Different procedures have been utilized to incorporate metal ions, such as silver, into DNA strands to construct metal nanostructures. Kasyanenko et al [ 76 ] bound bis(1,10-phenanthroline) silver(I) (Ag-Phen) to DNA in solution where the phenanthroline ligands allowed for uniform binding of silver on DNA structures. The Ag-Phen-DNA complexes were treated with sodium borohydride to reduce Ag metal on DNA fibrils.…”
Section: Metallization Of Dna Templatesmentioning
confidence: 99%
“…Covalent bonding involves the exchange of a labile ligand that is part of a coordination compound for one of the DNA bases [29] in which the N7 atoms of adenine and guanine are preferred [30] which affects the electron density of the heterocycles, causing instability of the DNA helix. The large number of binding sites disrupt the hydrogen bonding and stacking of nitrogenous bases [31]. Silver complexes can also bind to DNA through electrostatic binding to the phosphate backbone or binding in a major or minor groove of helix [32][33][34][35].…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14] The presence of the ligands in the silver complexes leads to the improvement of the silver function. 15 Moreover, the high number of Ag(I) center ions in a complex can improve the biological activity of silver complexes, 16 and the cytotoxic effect of binuclear silver(I) complexes is significantly more in cancer cells in comparison with the normal cells. 14 Haque et al showed that silver ions have a fundamental importance in the destruction of tumor cells.…”
Section: Introductionmentioning
confidence: 99%
“…3,12 Anticancer agents mostly act through the DNA molecule. 15 Molecules may interact with DNA by changing or preventing its operation, disordering gene sequencesand introde in transcription. 17 The main binding types in DNA complexes are covalent and non-covalent.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation